Infective endocarditis: surgical therapy - Fragomeni,Luís Sérgio de Moura (2003)
OBJECTIVE: To assess the major causes of surgical morbidity and mortality in patients with infective endocarditis operated upon in a regional cardiology center. METHODS: Thirty-four patients underwent surgical treatment for infective endocarditis. Their ages ranged from 20 to 68 years (mean of 40.6) and 79% were males. Their NYHA functional classes were as follows: IV - 19 (55.8%) patients; III - 12 (35.2%) patients; II - 3 (8.8%) patients. Blood cultures were positive in only 32% of the cases. Eight patients had already undergone previous cardiac surgery, whose major indication (82.3%) was heart failure refractory to clinical treatment. RESULTS: Four (11.7%) patients died at the hospital. Follow-up was complete in 26 (86%) patients. Five (14.7%) patients died later, 12, 36, 48, 60, and 89 months after hospital discharge. Of the 21 patients being currently followed up, 1 is in NYHA functional class III, and 5 in NYHA functional class II. CONCLUSION: A high degree of clinical suspicion, at an early diagnosis, and indication of surgical treatment prior to deterioration of left ventricular function and installation of generalized sepsis may improve prognosis.